Perioperative management and anaesthetic considerations for adult patients with Gilbert's syndrome and oral cancer: review and case report. Issue 1 (1st January 2019) - Tzoneva, Dochka; Aleksiev, Evgeniy; Michova, Kalina; Stanimirov, Pavel
Abstract: Gilbert's syndrome is the most common cause of hereditary hyperbilirubinemia and poses a clinical challenge for anaesthesiologists. The decreased activity of bilirubin uridine glucuronyl transferase can lead to toxicity for usual doses of most anaesthetic agents. We review and discuss the approach to successful and safe anaesthesia management in these patients and we report a case of a 48-year-old male patient with Gilbert's syndrome submitted to maxillofacial surgery under general anaesthesia. The recommended approach for the most successful and safe anaesthesia management in such patients includes the following: (i) minimizing the period of fasting to avoid hypoglycemia and dehydration; (ii) decreasing the perioperative stress by providing anxiolysis and adequate analgesia; (iii) avoiding hepatotoxic drugs and drugs predominantly metabolized by the liver; (iv) maintaining the hepatic blood flow; and (v) reduce polypharmacy.